Evaluation of porosity and permeability of sandstones within the Oti Group of the Volta Basin using petrophysical and petrographic techniques - Zobah, Theresa N.; Adenutsi, Casper D.; Amedjoe, Godfred C.; Wilson, Matthew C; Mensah, Emmanuel; Boateng, Cyril D.; Sarpong, Kwame K.; Opuni, Lydia N. O.; Danuor, Sylvester K.; Karimaie, Hassan (Journal of the Ghana Institution of Engineering, 2024)
This article is published in Journal of the Ghana Institution of Engineering (2023) 23:3 https//doi.org/10.56049/jghie.v23i3.100